HUBUNGAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR BIOLOGI PADA SISWA KELAS XI SMA NEGERI 1 TELUKDALAM - Lilis Karlina Gaurifa (Universitas Nias Raya, 2025)
This study aims to determine the relationship between students' learning interest and their academic achievement in Biology among Grade XI MIPA students at SMA Negeri 1 Telukdalam in the 2024/2025 academic year. The research employs a quantitative approach with a correlational method. The population consists of 108 students. Sampling was conducted using probability sampling with a simple random sampling technique, resulting in 52 students selected as the research sample. Data collection was carried out through questionnaires to measure students' learning interest and documentation of Biology learning outcomes. Data were analyzed using correlation statistics and t-test. Based on the statistical analysis, the calculated t-value was 4.9796, while the t-table value at a 5% significance level with 50 degrees of freedom was 1.67591. Since the t-calculated value is greater than the t-table value, it can be concluded that there is a significant relationship between students' learning interest and their Biology learning outcomes. In other words, the higher the students’ interest in learning, the better their academic performance in Biology tends to be. Suggestion: Schools and teachers are encouraged to enhance students’ learning motivation and implement effective teaching strategies that foster learning interest, such as interactive methods, engaging educational media, and consistent positive reinforcement to help improve student outcomes.